The Response of Seed Germination and Seedling Growth Of Papaya (Carica papaya L.) CV CALINA to The Concentration Treatments and The Duration of Seed Soaked In Coconut Water - Zainudin, Agus; Adini, Almas Adlina (Universitas Muhammadiyah Malang, 2019)
This research aimed to carry out the response of seed germination and seedling growth of Calina papaya to the seed soaked in coconut water. It was conducted from April to June 2017. The study comprised two designs of experiment i.e. the Completely Randomized Design for the seed germination and the Randomized Complete Block Design for the seedling growth of papaya. There were 25 treatment combinations obtained and each treatment was replicated three times. The treatment factors comprised the concentration and the duration of seed soaked in coconut water. The results showed that the seed immersion in the 80% concentration of coconut water for 8 hours had the highest growth rate and vigour index. Meanwhile, the seed immersion in the 60% concentration of coconut water for 8 hours showed the highest percentage of germination. The seed immersion for eight hours resulted in the seedling growth of papaya.